Students’ Aattitudes Toward Using Instagram in Teaching Writing - Fitri Handayani (Jurnal Educative: Journal of Educational Studies, 2017)
This study aims to investigate students’ attitudes towards the use of Instagram in teaching writing. This study was descriptive research which was carried out at English Department UMMY Solok. The population of the research was first grade students of English Department UMMY Solok who took Writing I subject. The total number of 8 students enrolled at the closed group feature of Instagram, in which only group members can interact each other. To get the data of the research, the researcher used questionnaire and interviewed. The research design included a 5 point Likert-type questionnaire which were strongly agree (SA), Agree (A), Undecided (U), Disagree (D), and strongly Disagree (SD). It was used to investigate students’ attitudes toward the use of Instagram in teaching writing. For the interview, the researcher prepared semi-structured interviews. It was done to five students who had randomly selected. The finding of the research showed that students had a very positive attitude towards the use of Instagram as an teaching writing activity in the classroom. Keywords: Instagram, Writing, Teaching Writing